Integration of prebend optimization in a holistic wind turbine design tool. Issue 6 (September 2016) - Sartori, L; Bortolotti, P; Croce, A; Bottasso, C L
Abstract: This paper considers the problem of identifying the optimal combination of blade prebend, rotor cone angle and nacelle uptilt, within an integrated aero-structural design environment. Prebend is designed to reach maximum rotor area at rated conditions, while cone and uptilt are computed together with all other design variables to minimize the cost of energy. Constraints are added to the problem formulation in order to translate various design requirements. The proposed optimization approach is applied to a conceptual 10 MW offshore wind turbine, highlighting the benefits of an optimal combination of blade curvature, cone and uptilt angles.